Innovative approaches for assessing and enhancing the hosting capacity of PV-rich distribution networks: An Australian perspective. (June 2022) - Rajabi, A.; Elphick, S.; David, J.; Pors, A.; Robinson, D.
Abstract: The rapid increase in the deployment of residential PV systems has caused various concerns for electricity network service providers in accommodating higher amounts of PV while maintaining the system operating indices at their acceptable ranges. This concept, usually referred to as hosting capacity (HC), has gained increased attention in recent years. This paper aims to address the state of the art in HC assessment and enhancement through a comprehensive examination of various research studies and practical projects. First, the main HC concepts, assessment methodologies, and practical implementation considerations are reviewed. Next, the novel technologies for HC enhancement are extensively discussed. Then, the important findings of various Australian trials are reported. Finally, the findings of the reviewed studies are summarised and the future directions are highlighted. Results of this paper can be used by both research efforts and industry practitioners for guiding the HC studies and enhancements. Highlights: The state of the art in hosting capacity of distribution grids are extensively discussed. The procedures for conducting hosting capacity studies are illustrated. Various hosting capacity quantification methods are explained. The novel solutions for improving the hosting capacity are discussed in detail. The findings of various Australian projects are summarised and reported.